2010
DOI: 10.1007/s00244-010-9569-3
|View full text |Cite
|
Sign up to set email alerts
|

Distribution of Organophosphorus Pesticides in the Bed Sediments of a Backwater System Located in an Agricultural Watershed: Influence of Seasonal Intrusion of Seawater

Abstract: This article focuses on the temporal and spatial distribution of three organophosphorous pesticides-malathion, methyl parathion, and chlorpyrifos-in the sedimentary environment of a backwater ecosystem, Kuttanad backwaters, situated in Kerala, India. Based on salinity distribution, geographic characteristics, and human activities prevailing in the area, the study area was divided into three zones: zone 1 with riverine characteristics, zone 2 with freshwater characteristics during and after the monsoon season a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(13 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…The farers of the region are spraying huge amount of this pesticide along with fertilizers to control different pests that results in an appreciable amount of methyl parathion in the water samples of Tighra reservoirs. The present study is in accordance with the results of Babu et al (2011) and Rehana et al (1995), who reported either absence of The overall concentration of dichlorovas is higher as compared to other organophosphorus pesticides as shown in Fig. 2.…”
Section: Choloropyrifossupporting
confidence: 96%
“…The farers of the region are spraying huge amount of this pesticide along with fertilizers to control different pests that results in an appreciable amount of methyl parathion in the water samples of Tighra reservoirs. The present study is in accordance with the results of Babu et al (2011) and Rehana et al (1995), who reported either absence of The overall concentration of dichlorovas is higher as compared to other organophosphorus pesticides as shown in Fig. 2.…”
Section: Choloropyrifossupporting
confidence: 96%
“…2 mg ml À 1 remained inhibitory. In order to assess the instantaneous effect (and not the long term effect), the tested doses were selected too high to be environmentally realistic doses [which ranges from 1 to 7 ng g À 1 sediment, 0.002-0.172 mg g À 1 soil and 0.607-1.121 mg L À 1 in ground water (Kumari et al, 2008;Babu et al, 2011)]. Further, the tested doses are relevant because at the time of exposure, farmers generally add pesticides more than the recommended dose.…”
Section: Chlorpyrifos and Uv-b Treatmentsmentioning
confidence: 99%
“…6) Several studies have reported the presence of MP and its metabolite residues in human food, vegetables, honey, milk, and processed products, such as yogurt. [7][8][9] In addition, MP has been reported in atmospheric samples, 10) sediment samples, 11) fresh water samples, 12) and marine water samples. 13) Furthermore, the e ects of MP on the behavior of bees have been reported at sublethal doses.…”
Section: Introductionmentioning
confidence: 98%